A Brief Resume on the Genus Lagerstoemia - Sinhababu, A.; Laskar, S.; Thakur, S.; Basak, B.K. (Asian Journal of Chemistry, 2010)
In this review, the different chemical compounds have been isolated from different plants of the genus Lagerstroemia (Family Lythraceae) are listed (till 1997 in chemical abstract and from some papers). This genus is characterised by different class of compounds, viz., alkaloids, steroids, terpenoids, anthocyanins, tannins, elagic acids, fatty acids, amino acids, proteins, etc. There are 64 references.